Who Governs Bank Stability Amid Crises? Evidence From Broad Characteristics, Risk, and Performance - Linda Putri Nadia; Izza Ashsifa; Izzat Firdausi; Anton Satria Prabuwono (Al-Amwal : Jurnal Ekonomi dan Perbankan Syari'ah, 2026)
Introduction: This study explores a relatively under-researched area in Indonesia, namely the influence of women board members on bank performance and risk. This study fills a crucial gap in the literature on the influence of board characteristics on bank risk-taking and performance in Indonesia, a country in Asia with characteristics distinct from those of European countries. We investigate the impact of board characteristics on bank risk and performance. Methods: We used unbalanced panel data comprising 594 bank-year observations from Bank Indonesia for 2003-2022 and tested the model using a fixed-effects model, controlling for bank and year effects  Results: This study found that women board members have a positive effect on bank performance and a negative impact on bank risk. On the other hand, we find robust results related to women directors have a positive impact on bank performance and a negative impact on bank risk, even though examined with different models and proxies. On the other hand, Board size positively affects bank stability but shows no consistent impact on credit risk or performance during crises. In contrast, board independence is negatively associated with stability and weakens bank performance during crisis periods. Conclusion and suggestion: This research can contribute to the government’s attention to the importance of gender diversity on boards of directors. These study results can also guide other developing countries with similar legal systems.